2006
DOI: 10.1016/j.exer.2005.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane induces apoptosis of interferon-γ activated macrophages in vitro

Abstract: Amniotic membrane (AM) used as a temporary or permanent graft for ocular surface reconstruction has a potent anti-inflammatory effect. We would like to investigate the mechanism whereby AM induces macrophage apoptosis in vitro. Mouse macrophages, Raw 264.7 cells, were cultured on plastic, type I collagen, corneal stromal slice or AM stromal matrix in serum-free medium with or without interferon-γ (IFN-γ). Cells were stained by LIVE/DEAD assay, Hoechst-33342, and TUNEL assay for cell death and apoptosis. Cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 33 publications
3
49
0
2
Order By: Relevance
“…2). Collectively, these data corroborate the previous studies based on AM (33,34,40) and AME (41) while beginning to explain the mechanism of their anti-inflammatory effects via promotion of apoptosis of activated neutrophils (33,34,37), macrophages (35,37,39), and probably lymphocytes (36).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…2). Collectively, these data corroborate the previous studies based on AM (33,34,40) and AME (41) while beginning to explain the mechanism of their anti-inflammatory effects via promotion of apoptosis of activated neutrophils (33,34,37), macrophages (35,37,39), and probably lymphocytes (36).…”
Section: Discussionsupporting
confidence: 79%
“…Application of cryopreserved human AM reduces infiltration of neutrophils in the excimer-ablated rabbit corneal stroma while promoting apoptosis of neutrophils (33,34); traps and causes apoptosis of monocytes and macrophages during the treatment of human corneal epithelial defects (35); induces rapid regression of corneal stromal edema and inflammation by reducing infiltration of lymphocytes (36), neutrophils (37), and macrophages (37,38); and promotes M2a phenotype in the corneal stroma of murine HSV-1 necrotizing keratitis (39). These in vivo data are supported by in vitro findings that human AM induces apoptosis of IFN-␥ activated monocyte/macrophage RAW264.7 cells (40).…”
supporting
confidence: 73%
“…Macrophages with ingested apoptotic cells markedly decrease expression of CD40, a co-stimulatory factor for T-lymphocytes (Barker et al, 1999) of proinflammatory cytokines and increased production of prostaglandin E2 and transforming growth factor-b1 (Fadok et al, 1998), both factors involved as regulators of physiological T cell homeostasis, activation, differentiation, and effector function. Recently, it has been shown that cells of a macrophage cell-line cocultured with AM only underwent apoptosis when activated with IFN-γ, while apoptosis was not found when IFN-γ was absent (Li et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of proteinase and MMP activation by amniotic membrane leads to decreased infiltration of inflammatory cells (Kim et al, 2000). Moreover, pro-apoptotic activity of the amniotic membrane was also reported -amnion can promote the apoptosis of leucocytes (Li et al, 2006;Zhou et al, 2003). Amniotic epithelial cells express the apoptosis-inducing genes Fas L, TNF, and TRAIL (Li et al, 2005).…”
Section: Properties Of the Amniotic Membranementioning
confidence: 99%